Development and Validation of Polypharmacy-Related Psychological Distress Scale (PPDS): A Preliminary Study - Cheng Cheng; Xiao Chen; Junqiao Wang; Martin Christensen (Behavioral Sciences)
Polypharmacy is an increasing concern in healthcare due to its potential to cause adverse drug reactions and medication non-adherence. The evidence has identified a connection between psychological distress and polypharmacy, yet there is a lack of validated instruments to measure this specific type of distress. This study aims to develop and validate the Polypharmacy-related Psychological Distress Scale. This study followed a rigorous scale development procedure, encompassing item creation, scale development, and scale evaluation. A multi-method design incorporated a literature review, the Delphi method with eight experts, and a cross-sectional survey with 97 participants. A comprehensive range of psychometric tests, including content validity, face validity, concurrent validity, internal consistency, and construct validity, were utilized to assess the goodness of the instrument—the finalized scale comprised four items. Content validity results were deemed satisfactory based on CVI for item (I-CVI) and CVI for scale (S-CVI). Face validity was established through the incorporation of participant feedback. A significant correlation was found between the Patient Health Questionnaire-4 and the Polypharmacy-related Psychological Distress Scale, with a correlation coefficient of 0.444 (p < 0.001). The scale demonstrated acceptable reliability, with a Cronbach’s alpha of 0.790 and a McDonald’s omega of 0.937. A confirmatory factor analysis revealed a unidimensional structure. To summarize, the Polypharmacy-related Psychological Distress Scale showed satisfactory reliability and validity in this preliminary study. It holds promise for use by healthcare professionals to assess psychological distress in the target population, pending further validation.